Budaya Sosial Masyarakat Postkolonial Jawa pada Masa Orde Baru dalam Novel Entrok Karya Okky Madasari - Fitri Nurul Afni, Fitri Nurul Afni (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
Javanese postcolonial society has a social culture that has become a habit of society as a result of the mixing of cultures of the colonial nations and the original culture of the community which has not changed. The postcolonial society in Entrok's novel is set in the New Order era which shows the reflection of Indonesian culture, especially Javanese postcolonial society. This article aims to identify the forms of social culture in post-colonial Javanese society during the New Order in the novel Entrok by Okky Madasari as a reflection of the life of Javanese people after experiencing colonialism by Western nations. The focus of the problem in this article is the culture or social behavior of the Javanese postcolonial people in the Entrok novel. The research methodology on this article uses the quantitative approach of the descriptive method, using data collection techniques in the form of literature study techniques. Data analysis techniques in this article are data reduction, data presentation, and conclusion. The results of this article find various social cultures of postcolonial Javanese society in Entrok's novel in the form of social class, gender inequality, discrimination, freedom of speech, extortion, and arbitrariness.